Polycystic ovary syndrome among Indian adolescent girls – A systematic review and metanalysis - Sharma, Megha; Khapre, Meenakshi; Saxena, Vartika; Kaushal, Pawna (Nepal Journal of Epidemiology, 2021)
Background: Polycystic ovary syndrome (PCOS) is a common endocrine disorder in the progenitive age group and the leading cause of infertility. The worldwide prevalence of PCOS in women varies between 2.2% to 26%. Due to limited literature on burden of PCOS among adolescent girls, its significance is still unfathomed as a research is few and far between in the present time. We conducted Systematic review and metanalysis to estimate the pooled prevalence of PCOS among Indian adolescent girls (14-19 years). Methods: With the help of a search strategy, two authors searched Scopus, Embase and Pubmed independently. We screened studies considering eligibility criteria and extracted data. Selected studies were assessed for quality and risk biases using the NIH tool. R software was used for analysis. Results: Twelve studies were included in the meta-analysis. The total number of participants in the study was 4473. All studies scored average and above as per the NIH quality assessment tool. The prevalence of PCOS among adolescents based on the Rotterdam criteria was 17.74 per 100 (CI = 11.77-23.71) with I² =97 %. Hospital-based studies had a comparatively higher prevalence of PCOS as compared to community-based. Conclusion: Pooled prevalence of PCOS among Indian adolescents' girls was high, approximately one in five.